Pengaruh Work-Life Balance dan Psychological Capital terhadap Retensi Karyawan - Hamy Wahjunianto; Erwin Tjahjuadi (LPPM STIE YAPAN, 2025)
Employee retention has become a critical issue in human resource management, as high employee turnover rates can result in significant losses for companies. Among the factors believed to influence employee retention are work-life balance and psychological capital. This study aims to analyze the effect of work-life balance and psychological capital on employee retention at JKM Sidoarjo, both partially and simultaneously. This study employs a quantitative approach using a survey method. The research population consisted of all 70 employees of JKM Sidoarjo, and a saturated sampling technique was therefore applied. Data were collected through a Likert scale questionnaire and analyzed using multiple linear regression with the assistance of SPSS. Prior to the main analysis, validity tests, reliability tests, and classical assumption tests were conducted. The results indicate that work-life balance has a positive and significant effect on employee retention, with a t-value of 4.196 and a significance level of 0.000. Psychological capital also exerts a positive and significant effect on employee retention, with a t-value of 5.442 and a significance level of 0.000. Simultaneously, both variables significantly influence employee retention, as evidenced by an F-value of 52.431 and a significance level of 0.000. The Adjusted R Square value of 0.598 indicates that both variables collectively contribute 59.8% in explaining the variation in employee retention. It is therefore concluded that improvements in work-life balance and psychological capital can effectively enhance employee retention within the company